2015
DOI: 10.1016/j.electacta.2015.07.109
|View full text |Cite
|
Sign up to set email alerts
|

Pd/Ni Synergestic Activity for Hydrogen Oxidation Reaction in Alkaline Conditions

Abstract: The investigation of hydrogen oxidation reaction (HOR) in alkaline conditions has been the subject of a wide interest in the past few years with the rise of alkaline membrane fuel cells (AMFCs). In particular, the quest for the lowest content of platinum group metals (PGMs) in the HOR catalyst is ongoing. In this article, we propose the use of a nanoscale Pd layer partially covering a Ni film to provide the most efficient use of the PGM in the HOR catalyst. The Pd/Ni electrodes were prepared by spontaneous and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 35 publications
4
35
0
Order By: Relevance
“…This value < 0.1mA/cm 2 Pd is the usual value for palladium in alkaline medium, this was corroborated in a similar study where a gold surface was covered by palladium [142]. Coming back to the Pd/Ni study, the highest exchange current values were obtained with a low Pd coverage, even above 1.5% on Ni (Figure 21 (red dots)) [140].…”
Section: Hydrogen Oxidation Reaction-horsupporting
confidence: 67%
See 2 more Smart Citations
“…This value < 0.1mA/cm 2 Pd is the usual value for palladium in alkaline medium, this was corroborated in a similar study where a gold surface was covered by palladium [142]. Coming back to the Pd/Ni study, the highest exchange current values were obtained with a low Pd coverage, even above 1.5% on Ni (Figure 21 (red dots)) [140].…”
Section: Hydrogen Oxidation Reaction-horsupporting
confidence: 67%
“…It was also determined that Pd/C catalysts, under the same work conditions conveyed values below 0.1 mA/cm 2 Pd at an overvoltage η = 0.05 V with a palladium loading of 5 μg/cm 2 [141], while Pd/Ni with 0.9 μg/cm 2 reaches 0.30 mA/cm 2 disc and 0.57 mA/cm 2 Pd at an overvoltage η = 0.05 V [120]. For Ni covered by a high amount of Pd, the exchange current density Recent papers have proposed the use of various nanoscale electrocatalysts, such as Ni films partially covered by a palladium layer which provide one of the most active materials for the HOR [140]. These Pd/Ni electrodes were synthesized by an electrolytic deposition of palladium over a polycrystalline Ni surface varying the composition of the surface.…”
Section: Hydrogen Oxidation Reaction-hormentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies in alkaline media have demonstrated that Pd is am ore effective catalystt han Pt. [21][22][23][24] Although Pd is also an oble and expensive metal,i ti sh alf the price of Pt and its combination with another co-catalyst may substantially improve its efficiency in ar eactiona nd reduce the costs of electrode materials. [25][26][27][28][29][30] In fact, PtRu and PdRu catalysts with controlled particle sizes weres hown to provide significantly improved catalytic performances toward some organic fuels.…”
mentioning
confidence: 99%
“…9 Therefore, the presence of H ab influences the kinetics of the hydrogen electrode reaction in their both directions, the cathodic hydrogen evolution reaction (her) and the hor, although it was not considered in most of the studies, where slow potentiodynamic sweeps were used. [10][11][12][13][14][15] Otherwise a work carried out on steady state in acid solutions, employing chronoamperometry, showed that the her is verified on βPd-H, while the hor involves both phases. 16 βPd-H is stable at low (η<0.05 V) and αPd-H at high overpotentials, being βPd-H better electrocatalyst.…”
mentioning
confidence: 99%